2017
DOI: 10.1007/s00420-017-1275-2
|View full text |Cite
|
Sign up to set email alerts
|

Is organizational justice climate at the workplace associated with individual-level quality of care and organizational affective commitment? A multi-level, cross-sectional study on dentistry in Sweden

Abstract: PurposeThe aim of this study is to investigate whether organizational justice climate at the workplace level is associated with individual staff members’ perceptions of care quality and affective commitment to the workplace.MethodsThe study adopts a cross-sectional multi-level design. Data were collected using an electronic survey and a response rate of 75% was obtained. Organizational justice climate and affective commitment to the workplace were measured by items from Copenhagen Psychosocial Questionnaire an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 72 publications
3
18
0
1
Order By: Relevance
“…Organizational justice had a direct effect on both work engagement and nursing care quality, which is similar to studies by Wan et al () and Berthelsen et al (). Organizational justice refers to the degree to which nurses perceive decision‐making procedures, interpersonal interactions, information exchanges and outcomes of work to be fair.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Organizational justice had a direct effect on both work engagement and nursing care quality, which is similar to studies by Wan et al () and Berthelsen et al (). Organizational justice refers to the degree to which nurses perceive decision‐making procedures, interpersonal interactions, information exchanges and outcomes of work to be fair.…”
Section: Discussionsupporting
confidence: 89%
“…A low level of organizational justice is related to lower work engagement (Gillet, Fouquereau, Huyghebaert, & Colombat, ; Wan, Zhou, Li, & Shang, ), higher job dissatisfaction (Ali, ) and burnout (Moliner, Martínez‐Tur, Peiró, Ramos, & Cropanzano, ). Berthelsen, Conway, and Clausen () found that perceived organizational justice at the unit level had a significant positive association with staff‐reported quality of care.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous multilevel study, we introduced such a measure based on three items. 13 The findings corroborated the validity and reliability of aggregating individual staff scores on care quality to report a mean score for each clinic. Also, the organizational justice climate at the clinic contributed to explain a substantial part of variation in staff assessment of care quality among clinics, thus linking the measure to the work environment.…”
Section: Introductionsupporting
confidence: 55%
“…() identify an association between organisational justice and affective commitment in frontline nurses working in Ontario, Canada. Similarly, a “just” climate at the clinical unit level is significantly associated with perceived quality of care and affective commitment to the organisation in a sample of dental nurses in Sweden (Berthelsen, Conway, & Clausen, ). A study of nurses in Urmia also identify a relationship between justice perception and organisational commitment (Mahmoudi, Hassani, & Aghlmand, ).…”
Section: Theorymentioning
confidence: 99%